Sexualidade e envelhecimento: a demanda de atualização de crenças e valores - Costa, Ana Carolina de Oliveira (2008)
This research s goal is to understand the significance of the experience of the sexuality during the aging process through an investigation of the values and beliefs linked to the sexual life and how they were built along the years. Starting from a perspective of development of the vital cycle, we established psychobiological aspects and later the historic and cultural aspects concerning aging and sexuality. The amount of information was gathered during three sessions focusing on the theme, obtained from a psycho therapeutic group with main focus on questions pertaining aging. This group had 12 participants with ages between 55 and 79 years old and the sessions lasted for a year. We could identify that the participants deal differently with the consciousness of the aging process but the majority of them was able to reshape their values and beliefs concerning the body trough their own individual experiences. While sexuality is taken in context only within the bounds of marriage it shows the presence of aggregated values of the marriage duration, where the quality of the relation is related mostly concerning the duration or even if they had lasting unions they were less concerned with the focus on conjugal satisfaction. It was possible to identify a conflict between the wish to attain a quality relation and the experience of an unsatisfactory relation, where they were not able to reshape values and beliefs and the relation itself